Analysis of Economic Factors Affecting the Developments in Livelihood-based Housing in Rural Areas (Case study: Mojezat County, Zanjan Township) - Leila Eslami; Behroz Mohammadi Yeganeh; Mehdi Cheraghi (مسکن و محیط روستا, 2019)
Rural housing as the main physical element of space with a multi-functional nature has been constantly evolving influenced by various factors and forces. The most important components that have changed in recent years in the context of housing-related developments are the housing component in the rural areas. The shift from livelihood-based housing to rural housing, which has only a residential function, has a negative impact on the rural economy. In this regard, this study aims to identify the status of housing in rural areas and to answer the following questions: 1. What is the livelihood situation of rural housing in the studied villages?  2. Which economic indicators affect living-based housing in the studied villages? In the present study, the analysis and ranking of components of Livelihood -based housing in rural areas will be discussed., The nature of the descriptive - analytic and the type of application, data collection method used for the study was “library and field method” (questionnaires and interviews). Data analysis was descriptive (Mean and standard deviation) and inferential statistics (Binomial test and multivariate regression) and the Vicor model. The questionnaire is composed of closed questions and answers on Likert five scale. The statistical population is 3464 in the Mojezat County. According to Cochran's formula were selected 321 households in 7 rural, as the sample size. Also, Cronbach's alpha was used to measure the reliability of the indices, with the values of 0.939 percent for economic factors and 0.867 percent for the livelihood housing component. The findings from the research show that the ratio of observation in the productive and logistic components of rural housing in the studied areas is low compared with the test ratio, as well as the ratio of observation in biological, social and cultural components compared with the test ratio, Is located on the upper level. The results also show that there is a direct correlation between the indicators of economic and livelihood of rural houses. At a significant level of 0.05, the variables of financial capital and credits, with the values of 0.467, 0.317, had the highest share in the dependent variable analysis of variance (rural housing function), the variables of income, employment, production method, type of production activity and ability have not been able to have a significant effect on the dependent variable. Finally, the results of the decision-making model of VIKOR for the study of economic indicators show that the villages of Gojeghia and Aghdehatoo villages with 1 and 0.453 have the highest Qi in the first and second rank respectively and the villages of Barotagaji (0.065) and Razbin (0.044) the lowest Qi is ranked sixth and seventh. In the past, according to the economic status and social classification of villagers, housing was made in different dimensions and sizes; But now, with the collapse of social classifications in the villages and the expansion of village communication with other settlements in the community, each village builds its home, regardless of the economic base, in the village, according to its will And in such a way that the low-income and vulnerable sectors of the rural community have a better and bigger venue than villages and villagers. The development of Livelihood-based housing has left out the monopoly of the economic factor and questioned its unconditional and contingent effect.